Museum Prabu Geusan Ulun Kabupaten Sumedang Sebagai Daya Tarik Wisata Kabupaten Sumedang - Gantina, Devita; Budiman, Surya Fajar; Nurbaeti, Nurbaeti; Gunawijaya, Jajang (Jurnal Ilmiah Pariwisata, 2021)
The Prabu Geusan Ulun Sumedang Museum is located in the city center of Sumedang district which was established in 1950. Not only as a place to store archaeological objects, but also the museum can be used as a tourist destination for history and culture education in Sumedang Regency. This study aims to determine the management of the Prabu . Museum Geusan Ulun in managing collections, and authenticity, as well as preserving heritage tourist attractions. This research is qualitative, where data collection is done directly through observation, interviews, and documentation. From the results of the study that the Prabu Geusan Ulun museum is very likely to be one of the icons of historical tourism in Sumedang district, but it is necessary to do some other activities or attractions so that the museum is visited by tourists from both the Sumedang district community and people outside Sumedang. Historical and cultural education tours at the Prabu Geusan Ulun Museum are expected to improve the economy of the people of Sumedang Regency. Keywords: Tourism, Prabu Geusan Ulun Museum, History, Culture